Restorative justice as a mechanism for horizontalization of penal conflicts and recognition of victims as subjects of rights - Magalhães Barros Bolzan de Morais, Flaviane de (2019)
This article discusses the need to overcome the criminal procedural model based on the neutralization of the victim and the consequent expropriation of the conflict by the State, as the only formula for solving the criminal case.Focusing on this procedural model, it is questioned whether its logic actually meets the needs of victims, respecting their fundamental rights and guarantees. The next question is about the urge to discuss, even in a way that is compatible with the current model, a new model of consensual solution of criminal conflicts, marked by the construction of dialogical and horizontal procedures as a response to crime. This article is based on the notion of horizontal justice, pointed out by Nils Christie, which demonstrates the importance to build a justice that fits the specificities of the central characters of the criminal conflict – offenders and victims – to a participative decision of the criminal case. Finally, it is analyzed if the Restorative Justice has sufficient potential to confer the necessary autonomy to the victims so that they are effectively understood as subject of rights.